A Rhizobium meliloti lipopolysaccharide mutant altered in competitiveness for nodulation of alfalfa - Lagares, Antonio (1992)
A transposon Tn5-induced mutant of Rhizobium meliloti Rm2011, designated Rm6963, showed a rough colony morphology on rich and minimal media and an altered lipopolysaccharide (LPS). Major differences from the wild-type LPS were observed in (i) hexose and 2-keto-3-deoxyoctonate elution profiles of crude phenol extracts chromatographed in Sepharose CL-4B, (ii) silver-stained sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis patterns of crude and purified LPS fractions, and (iii) immunoreactivities otherwise present in purified LPS of the parental strain Rm2011. In addition, Rm6963 lost the ability to grow in Luria-Bertani medium containing the hydrophobic compounds sodium deoxycholate or SDS and showed a decrease in survival in TY medium supplemented with high calcium concentrations. The mutant also had altered symbiotic properties. Rm6963 formed nodules that fixed nitrogen but showed a delayed or even reduced ability to nodulate the primary root of alfalfa without showing changes in the position of nodule distribution profiles along the roots. Furthermore, 2 to 3 weeks after inoculation, plants nodulated by Rm6963 were smaller than control plants inoculated with wild-type bacteria in correlation with a transient decrease in nitrogen fixation. In most experiments, the plants recovered later by expressing a full nitrogen-fixing phenotype and developing an abnormally high number of small nodules in lateral roots after 1 month. Rm6963 was also deficient in the ability to compete for nodulation. In coinoculation experiments with equal bacterial numbers of both mutant and wild-type rhizobia, only the parent was recovered from the uppermost root nodules. A strain ratio of approximately 100 to 1 favoring the mutant was necessary to obtain an equal ratio (1:1) of nodule occupancy. These results show that alterations in Rm6963 which include LPS changes lead to an altered symbiotic phenotype during the association with alfalfa that affects the timing of nodule emergence, the progress of nitrogen fixation, and the strain competitiveness for nodulation.